Character Education Through the Student Association Organization at the Musthafawiyah Purba Baru Islamic Boarding School - Abdul Kodir Jailani; Muhammad Kosim; Fauza Masyhudi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The purpose of this study is to find out the history of the KBM ALS santri association organization, the activities of the KBM ALS santri association organization that are oriented towards character education and the character values ​​instilled in the activities of the KBM ALS santri association organization. This type of research is descriptive using a Qualitative approach. The informants of this study are administrators, advisors, coaches and alumni of the KBM ALS santri association organization. Data collection techniques use observation, interviews and documentation. Based on the results of this study it is known that the KBM ALS santri association organization was founded in the 1960s with the name IPMAL then changed its name to YAGAMAL and finally became KBM ALS until now. The activities of the KBM ALS santri association organization that are oriented towards character education consist of tabligh, yasinan, mudzakarah, deliberation, Commemoration of Islamic Holidays (PHBI), takziyah and regulation of the union law. There are 18 character values ​​instilled in the activities of the KBM ALS student association organization, namely: religious, honest, tolerant, disciplined, hard working, creative, independent, democratic, curiosity, national spirit, love of the homeland, respect for achievement, friendly/communicative, love of peace, love of reading, care for the environment, care for society and responsibility. This research is expected to be a motivation for students to increase their activeness in participating in their respective regional organizations because by actively participating in organizations it can shape good student character.